Abnormal gut microbiota and bile acids in patients with first‐episode major depressive disorder and correlation analysis. Issue 7 (23rd May 2022) - Sun, Ning; Zhang, Jie; Wang, Jizhi; Liu, Zhifen; Wang, Xin; Kang, Pengli; Yang, Chunxia; Liu, Penghong; Zhang, Kerang
Abstract : Aim: Gut microbiota and its metabolite bile acids may play a significant role in the occurrence and development of major depressive disorder (MDD). Therefore, this study analyzes gut microbiota and bile acids, as well as their correlation in patients. Methods: Thirty‐one patients with MDD and 29 healthy controls (HCs) were enrolled in this study. We collected their both blood and feces. Plasma bile acid content was determined by liquid chromatography‐mass spectrometry and gut microbiota was detected by 16SrRNA gene sequencing and subsequently analyzed. We also analyzed the correlation between different gut microbiota, bile acids, and Hamilton Depression (HAMD) score. Results: The α‐diversity analysis found that Simpson and Pielou evenness index was much higher in HCs than in the patients with MDD. The β‐diversity of the two groups were differences by nonmetric multidimensional scaling analysis. Linear discriminant analysis effect size analysis identified 16 different strains. Bile acids detection showed that 23‐nordeoxycholic acid in patients with MDD was significantly higher than in HCs, whereas taurolithocholic acid (TLCA), glycolithocholic acid (GLCA), and lithocholic acid 3‐sulfate were significantly lower. Spearman correlation analysis showed that Turicibacteraceae, Turicibacterales, and Turicibacter were positively related with TLCA, GLCA, glycodeoxycholic acid (GDCA), and taurodeoxycholic acid, and were negatively correlated with HAMD score. At the same time, TLCA, GLCA, and GDCA were negatively correlated with HAMD score. Conclusions: Gut microbiota and bile acids metabolism are disturbances in MDD, and there exists a correlation between gut microbiota and bile acids metabolism. Moreover, their interaction may be related to the pathophysiological mechanism of MDD.